2005
DOI: 10.1038/sj.bmt.1705108
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and correlates of cognitive functioning following bone marrow transplantation

Abstract: Summary:Patients who undergo bone marrow transplantation (BMT) often report cognitive problems following treatment. This study used cognitive tests and a self-report measure of subjective cognitive complaints to determine (1) the rate of objective cognitive impairment in a sample of 65 BMT patients, and (2) the correspondence of patients' cognitive complaints to their actual cognitive performance. At 6 months following BMT, patients were assessed in seven cognitive domains -attention, verbal learning, verbal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 21 publications
6
47
3
2
Order By: Relevance
“…2 Studies to date have mostly used measures of general cognitive ability (for example, intelligence quotient (IQ)) rather than measuring specific cognitive functions, but it has been suggested that the executive functions of attention, concentration and working memory may be particularly associated with social difficulties. 5,12 Executive dysfunction has been shown to be the most frequent cognitive impairment in adult HCT survivors, 13,14 but has not yet been investigated in children. In addition, executive abilities and social function have been shown to be associated in childhood psychiatric disorders, such as attention deficit hyperactivity disorder, 15 conduct disorder 16 and autism.…”
Section: Introductionmentioning
confidence: 99%
“…2 Studies to date have mostly used measures of general cognitive ability (for example, intelligence quotient (IQ)) rather than measuring specific cognitive functions, but it has been suggested that the executive functions of attention, concentration and working memory may be particularly associated with social difficulties. 5,12 Executive dysfunction has been shown to be the most frequent cognitive impairment in adult HCT survivors, 13,14 but has not yet been investigated in children. In addition, executive abilities and social function have been shown to be associated in childhood psychiatric disorders, such as attention deficit hyperactivity disorder, 15 conduct disorder 16 and autism.…”
Section: Introductionmentioning
confidence: 99%
“…The deficits in psychomotoric skills persisted until the third measurement, which the authors associated with chronic graft-versus-host disease (GvHD) and the longterm immunosuppression associated therewith. BoothJones et al 39 examined 65 patients 6 months after HSCT, finding at least mild cognitive deficits in 51% and moderate-to-severe impairment in 28%. The predictors for impaired neuropsychological test performance were lower premorbid intelligence and advanced age.…”
Section: Introductionmentioning
confidence: 99%
“…In survivors by time improvement spontaneously occurs but generally not to the norm observed in healthy subjects. Also in other cancers than hematological malignancies cognitive impairment after treatment has been reported [5,13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Booth-Jones et al, examined 65 patients with breast cancer, leukemia, lymphoma and multiple myeloma 6 months after transplantation in seven cognitive domains, including attention, verbal learning, verbal memory, visual memory, simple executive function, complex executive function and psychomotor speed [5]. 51% had mild cognitive impairment and 28% moderate or severe impairment.…”
Section: Cognitive Impairment Associated With Hematopoietic Cell Tranmentioning
confidence: 99%